2014
DOI: 10.1038/nature13899
|View full text |Cite
|
Sign up to set email alerts
|

Structural insight into autoinhibition and histone H3-induced activation of DNMT3A

Abstract: DNA methylation is an important epigenetic modification that is essential for various developmental processes through regulating gene expression, genomic imprinting, and epigenetic inheritance. Mammalian genomic DNA methylation is established during embryogenesis by de novo DNA methyltransferases, DNMT3A and DNMT3B, and the methylation patterns vary with developmental stages and cell types. DNA methyltransferase 3-like protein (DNMT3L) is a catalytically inactive paralogue of DNMT3 enzymes, which stimulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
304
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 311 publications
(342 citation statements)
references
References 42 publications
18
304
0
Order By: Relevance
“…The Tet2 protein we used is purified from HEK293T cell and the amount of Tet2 protein is limited. In addition, the newly published data (Guo et al, 2015) indicate that Tet proteins are evolutionarily tuned to be less reactive towards 5hmC, therefore the generation of 5fC and 5caC is far less than 5hmC. When we increase the amount of Tet2 protein in enzymatic activity, we found that 5fC and 5caC can be detected, moreover, the amount of 5fC and 5caC increased with the addition of MBD3L2 in vitro.…”
Section: Mbd3 and Mbd3l2 Co-occupy Chromatin With Tet2mentioning
confidence: 59%
“…The Tet2 protein we used is purified from HEK293T cell and the amount of Tet2 protein is limited. In addition, the newly published data (Guo et al, 2015) indicate that Tet proteins are evolutionarily tuned to be less reactive towards 5hmC, therefore the generation of 5fC and 5caC is far less than 5hmC. When we increase the amount of Tet2 protein in enzymatic activity, we found that 5fC and 5caC can be detected, moreover, the amount of 5fC and 5caC increased with the addition of MBD3L2 in vitro.…”
Section: Mbd3 and Mbd3l2 Co-occupy Chromatin With Tet2mentioning
confidence: 59%
“…DNMT3A contains three functional domains: a PWWP domain, an ADD domain and a C-terminal DNA methyltransferase (MTase) domain 16. Mutants were mapped onto the active and autoinhibited form of the DNMT3A-DNMT3L complex (Protein Data Bank (PDB) 4U7T and 4U7P).…”
Section: Methodsmentioning
confidence: 99%
“…Given the known functional interaction between DNA methylation and histone modifications, these alterations were intriguing. [13][14][15][16] The observed overexpression of the histone 3, lysine 79 (H3K79) methyltransferase, Dot1l (disrupter of telomere silencing 1-like), was especially interesting because it plays a critical role in leukemia with MLL rearrangements. [17][18][19][20] Pharmacologic inhibition of DOT1L has shown promising preclinical activity in MLL-rearranged leukemia and is now being tested in adult and pediatric clinical trials.…”
Section: Introductionmentioning
confidence: 99%